Impact Evaluation on the Religious Practices on Honoring the Dead - Julio Ramillo A. Mercurio (Applied Quantitative Analysis, 2022)
Filipinos’ deep respect for the dead impelled the establishment of a culture of holding wake, interment and memorial as expression of reverence and tribute. Although Filipinos’ daily life are influenced by Catholic teachings, there is an observable lack of knowledge of and formation in the faith. This research investigated on the impact of religious practices on honoring the dead to selected Senior High School students of “X” College. Significant difference on the religious practices on honoring the dead – and on its extent of impact presented to the respondents in Christian Living lessons – in relation to the economic status and place of residence, were evaluated. Utilizing descriptive-evaluative design, findings of this study showed that, when grouped according to demographic profile, there is no statistically significant difference, both on (a) religious practices experienced by the respondents on honoring the dead and, (b) on its extent of impact as these religious practices are presented in Christian living lessons. A “Suggested Learning Resource” was crafted, highlighting in every lesson the indicators in the research questionnaire that received low WAM. It was concluded that the indicators which express the cultural aspect of the religious practices on honoring the dead were ranked least by the majority of the respondents, including indicators which express sense of belongingness in the family of God, ministry of consolation by all the baptized, and Christ as the center of our life. By integrating the “Suggested Learning Resource” in the existing learning package for Religious Education, crafting of lessons which are responsive to the educational and social context of learners – specifically on topics that touches Catholic doctrines on life, death and afterlife – will aim at a deeper appreciation of Catholic doctrines, leading to authentic witnessing to the Faith through one’s own cultural identity.